Enhancing students' relational understanding through the development of higher order thinking skills (HOTS)-based student worksheet - Sari, Desi Kurnia; Aisyah, Nyimas; Hapizah, Hapizah (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Relational comprehension represents a critical skill that students should acquire to correctly associate concepts. This investigation aims to cultivate a High Order Thinking Skills (HOTS)-based Student Worksheet that is both valid and practical, as well as effective, with the potential to significantly influence the relational comprehension of senior high school students. The 'design research' method, incorporating a 'formative research' development model, is used in this research, which is broken down into two stages: initial assessment and self-review. This study was carried out at Muhammadiyah 1 High School in Palembang, focusing on tenth-grade students. Data was evaluated qualitatively in a descriptive manner, founded on observations, interviews, and tests. The study's findings highlight that the developed HOTS-based student worksheet is valid, practical, and efficient in boosting students' relational comprehension once implemented in the classroom. The test outcomes indicate that students possess a reasonably good ability to comprehend HOTS category C4 problems, but are lacking in understanding HOTS category C5 problems. Therefore, additional research is deemed necessary to enhance students' understanding of HOTS category C5 problems.